Effect of sowing dates on different rapeseed varieties under rain fed condition - Ranabhat, Gaurav; Tiwari, Pramod; Dhakal, Ashmita; Oli, Pramod; Chapagain, Amira; Neupane, Susmita (Journal of Agriculture and Natural Resources, 2021)
Rapeseed is a leading oilseed crop of Nepal occupying 85% of total oilseed cultivation area. This research was conducted to determine the response of different sowing dates on different rapeseed varieties in their final yield under the rain fed condition in Phulbari, Dang. Two rapeseed varieties Unnati and Surkhet Local on three dates of sowing Oct 4, Oct 24 and Nov 14 were tested under two factorial RCBD design in the year 2018 A.D. Data consisted growth attributes like plant height, branch per plant, no. of siliqua per plant, aborted siliqua and siliqua abortion percentage and yield attributes such as biological yield, biomass yield, seed yield, harvest index and test weight. Statistically no difference was found between varieties whereas differences were found on different sowing dates. Result showed that among the varieties, the highest yield (8.59 q/ha) was obtained in Surkhet Local than in Unnati (8.54 q/ha). In case of sowing dates, higher seed yield was obtained in Oct 4 sown crop (15.93 q/ha) followed by Oct 24 (7.47 q/ha) and Nov 14 (2.29 q/ha).The higher seed yield obtained in early sowing is due to shorter vegetative and longer reproductive phase. The comparison of mean values of the seed yield for interaction between variety and sowing date showed that variety Surkhet Local sown in Oct 4 plant had the highest seed yield (16.33 q/ha) followed by variety Unnati on same sowing date (15.54 q/ha). Based on the result obtained, Surkhet Local*Oct 4 performed better in Dang condition.